Niat al-Muqaranah al-Hakikiyyah dan al-Muqaranah al-Urfiyyah dalam Ibadah Shalat Perspektif Ulama Syafiiyyah - Imam Syafi'i (AL-ISTINBATH : Jurnal Hukum Islam, 2019)
This research aims to examine and analyze the opinion of Syafi'iyyah scholars about intention in prayer. On this problem, Syafi'iyyah scholars are divided into two opinions, namely from the previous period scholars (Mutaqoddimin) whit his opinion intention of al-Muqoronah al-Hakikiyyah, and from the contemporary scholars (mutaakhkhirin) whit his opinion intention of al-Muqoronah al-Urfiyyah. This research is important because the intention in prayer is compulsory case (rukn) and is the beginning of all forms of worship. Other than that many Muslims doubt in his intention so anxiety arises in them. As research that examines the opinions of the scolars, the method used in this research is library research which descriptive qualitative research, where the object of study is literature in the form works in the yellow books, journal and other books. From the explanation and studies that has done, the intention of al-Muqoronah al-Hakikiyyah as stated by the previous period scholars is a law of origin, one must do when praying. Whereas the intention of al-Muqoronah al-Urfiyyah as stated by the contemporary scholars is rukhsah wajibah because of the udzur that befell a person while doing the prayer.